(3eMGVQGJ aj GdJMdjd GdGbJUGOj Gdcdj (B:s (3fXQjGJ hfeGPL GdJhGRf hGddGJhGRf (B/s - (3GdeGf, eMeO GdTQjas ((3GdLRGFQ(B: s (3efThQGJ HQJj(B, s, 1994)
(3GdfehPL GdcdGSjcj aj GdJhGRf GdGbJUGOj Gdcdj, GdfehPL GdcjfRj GdHSjW aj GdJhGRf GdGbJUGOj Gdcdj, GdJhGRf GdeJRGef dShb GdSdY hGdNOeGJ hGdfbO, GdfXQjI (B"(3GdGfOeGLjI(B" (3Ch eXQjI GddGJhGRf GdGbJUGOj Gdcdj(B: (3GdfehPL GdeQLYjs
(3GdeQGLY U(B.358s
Keywords: (3GdEbJUGO GdJMdjdjs